2023
DOI: 10.3145/epi.2023.mar.09
|View full text |Cite
|
Sign up to set email alerts
|

Which of the metadata with relevance for bibliometrics are the same and which are different when switching from Microsoft Academic Graph to OpenAlex?

Abstract: With the announcement of the retirement of Microsoft Academic Graph (MAG), the non-profit organization OurResearch announced that they would provide a similar resource under the name OpenAlex. Thus, we compare the metadata with relevance to bibliometric analyses of the latest MAG snapshot with an early OpenAlex snapshot. Practically all works from MAG were transferred to OpenAlex preserving their bibliographic data publication year, volume, first and last page, DOI as well as the number of references that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(3 reference statements)
1
3
0
1
Order By: Relevance
“…However, in that moment, all the records came from MAG, we accordingly suppose that OpenAlex would not provide more information than the reported by MAG. A recent publication, testing differences between MAG and OpenAlex, showed that, in the early moments, OpenAlex was just a MAG mirror enriched with Crossref's DOIs (Scheidsteger & Haunschild, 2023), being in line with our preliminary results.…”
Section: Research Implicationssupporting
confidence: 90%
“…However, in that moment, all the records came from MAG, we accordingly suppose that OpenAlex would not provide more information than the reported by MAG. A recent publication, testing differences between MAG and OpenAlex, showed that, in the early moments, OpenAlex was just a MAG mirror enriched with Crossref's DOIs (Scheidsteger & Haunschild, 2023), being in line with our preliminary results.…”
Section: Research Implicationssupporting
confidence: 90%
“…Currently this method is expensive to develop and hard to evaluate, but there are several providers of ready-made semantic classifications of disciplines. This study uses the OpenAlex database (OA), which has large coverage and is easily available to the public through an API (Aria and Le, 2023;Scheidsteger and Haunschild, 2023;Velez-Estevez et al, 2023). OpenAlex consists of lists of five types of entities: works i.e.…”
Section: Semantic Scores Of Disciplinarity and Granularity Of Taxonomiesmentioning
confidence: 99%
“…Dimensions (Herzog, et al, 2020) has a two-level hierarchy of Fields of Research with 22 main categories and 154 sub categories. OpenAlex has a six-level hierarchy of concepts with 19 toplevel categories and 284 second-level categories (Scheidsteger & Haunschild, 2023). In the case of Dimensions and OpenAlex, we used the second-level (sub) categories for the fieldnormalization because of their similar granularity compared to the journal-based schemes.…”
Section: Subject Classificationsmentioning
confidence: 99%